How to Promote Cooperative and Social Economy Ecosystems through Public Policies: The Valencian Case - Catala, Belén; Savall, Teresa; Chaves-Avila, Rafael (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale)

(untitled) (SFU Canadian Institute for Studies in Publishing, 2025)
For the social economy to reach its potential to generate inclusive prosperity, it must be embedded in supportive ecosystems. The question arises whether, from a public policy perspective, government policies can effectively activate and promote such ecosystems. This article addresses the nature of social economy ecosystems, identifies key elements of a public policy aimed at promoting them, and investigates whether this action increases their institutionalization in a territory. To this end, following the presentation of a theoretical framework, an analysis focuses on a case of public policy to promote the cooperative ecosystem, the “Plan Fent Cooperatives” of the Valencian Community. The results indicate that this strategy, described as a second-generation public policy for the promotion of the social economy, contributes to consolidating a favourable cooperative ecosystem in the region.